2017
DOI: 10.21037/jgo.2017.04.04
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative accuracy of gastric cancer staging in patient selection for preoperative therapy: race may affect accuracy of endoscopic ultrasonography

Abstract: Background: Over the last 15 years, large randomized controlled studies have validated the benefit of preoperative therapy for patients with resectable gastric cancer. Computed tomography (CT) and endoscopic ultrasonography (EUS) are commonly used to select patients for preoperative treatment, but studies of preoperative staging accuracy that focus on patient selection for preoperative therapy are rare; therefore, whether CT or EUS can reliably identify patients eligible for preoperative therapy is still uncle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 23 publications
4
16
0
Order By: Relevance
“…Several studies have mentioned the sensitivity for SM2 or deeper EGC by EUS ranging from 66.3% to 84.0%, 17 , 20 , 21 similar to the findings in our study.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Several studies have mentioned the sensitivity for SM2 or deeper EGC by EUS ranging from 66.3% to 84.0%, 17 , 20 , 21 similar to the findings in our study.…”
Section: Discussionsupporting
confidence: 91%
“…In some previous reports, EUS examinations were performed by conventional EUS or miniature probe. 20 , 21 , 23 This is one of the reasons that the upper-third stomach location was not a risk factor of misdiagnosis in our study, because it is often difficult to scan lesions located in the upper-third of the stomach using conventional EUS, while we have used only the miniature probe for EUS examination. The “0-I” macroscopic subtype has also been reported to be a factor for misdiagnosis, 13 , 15 however, macroscopic features had no relationship to misdiagnosis in our study.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…This finding contrasts with previous findings by Zanoni et al who analyzed patients with esophageal cancer and found that patients with “downstaged N0” disease had worse OS than those with “natural N0” disease, although the study did have a limited number of patients. The limited survival impact of cN status may be caused by inaccuracy of preoperative cN staging in gastric cancer patients, as reported before; however, such inaccuracy surely exists in the real world and needs to be taken into account. On the basis of the available data, achievement of ypN0 status appears to be an important predictor of good OS in gastric cancer.…”
Section: Discussionmentioning
confidence: 89%
“…Another aspect our study reveals is the importance in recognizing the established limitations of preoperative staging in reliably identifying early stage disease. Ikoma et al demonstrated limited accuracy of EUS at determining actual T stage, as well as both computed tomography (CT) and EUS having low sensitivities in determining N status [37]. We feel that under-staging may have contributed to the relatively large number of early stage patients with peritoneal carcinomatosis, and therefore we have limited confidence in foregoing peritoneal staging based on preoperative staging.…”
Section: Discussionmentioning
confidence: 92%